Development of HOTS Literacy-Based e-Student Worksheet for Acid-Base Materials - Vrili Coirala Rama Uli Br Siregar; Iis Siti Jahro (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2023)
Higher-order thinking skills (HOTS) and science literacy are skills that must be mastered by students in 21st-century learning. However, the learning resources are still not available so their HOTS Literacy skills are still low. This research is development research with the 4D model (define, design, develop, and disseminate). The research objectives are analyzing the Student Worksheet that has been used; designing an e-Student Worksheet based on HOTS Literacy; assessing the feasibility of the e-Student Worksheet; and determining the response of students. The research subjects were validators and students of class XI MIPA SMA Negeri 14 Medan. Data collection used questionnaires, teacher interviews and test instruments. The results are the feasibility of the e-Student Worksheet is 88.8% and interpreted as a very high criterion. The student’s response is 99.7% with very interesting criteria. The n-gain value is 0.71 with high criteria. This shows that the HOTS Literacy-based e-Student Worksheet for Acid-Base materials developed is feasible and effective in improving students’ HOTS Literacy skills.